2020
DOI: 10.1186/s12913-019-4878-3
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric nurses’ general self-efficacy, perceived organizational support and perceived professional benefits from Class A tertiary hospitals in Jilin province of China: the mediating effect of nursing practice environment

Abstract: Background: General self-efficacy is considered one of the most influential parameters affecting the quality of clinical practice and nurses' perceived professional benefits (NPPB). Perceived organizational support (POS) is regarded as being central in understanding job-related attitudes, and it is important to enhance POS for nurses to maintain their current employment. NPPB can further reduce nurses' job burnout and turn-over intention. Many studies have explored the relationships among general self-efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 44 publications
5
31
0
3
Order By: Relevance
“…This finding was in the same line with Cheng et al, [34] who mentioned that the mean and SD of nursing practice environment score was (91.33 ± 9.04). Moreover, the finding was congruent with Al Moosa, et al, [12] who stated that the total mean score of practice environment was moderate (M=2.9, SD=0.47), considering the majority of the respondents are staff nurses who routinely work at the bedside with patients, this relatively high mean score suggests favorability of practice environments.…”
Section: Discussionsupporting
confidence: 90%
“…This finding was in the same line with Cheng et al, [34] who mentioned that the mean and SD of nursing practice environment score was (91.33 ± 9.04). Moreover, the finding was congruent with Al Moosa, et al, [12] who stated that the total mean score of practice environment was moderate (M=2.9, SD=0.47), considering the majority of the respondents are staff nurses who routinely work at the bedside with patients, this relatively high mean score suggests favorability of practice environments.…”
Section: Discussionsupporting
confidence: 90%
“…The GSE scale has 10 items with a 4-point choice scale ranging from "1 = not at all true" to "4 = exactly true" [23]. GSE has been validated and used in several studies among undergraduate nursing student [24,25] and among registered nurses [26][27][28]. The internal consistency of the GSE in this study was good (Cronbach's alpha = 0.85).…”
Section: Self-efficacymentioning
confidence: 90%
“…Nursing professional self-efficacy had the greatest direct effect on explanation, and the largest total effect on attitude to families' importance in nursing care and nurse-parent partnership. Cheng et al [32] reported that the higher the self-efficacy perceived by pediatric nurses, the higher the professional perception, and the better the relationship between nurses and patients. Alavie et al [26], in their analysis of the concept of pediatric nurses' care self-efficacy, highlighted the importance of the provision of sufficient explanations to hospitalized children and their families, which improves the self-efficacy of child care to such a degree that FCC is fully implemented.…”
Section: Discussionmentioning
confidence: 99%